The Impact of Serum Oestradiol and Progesterone Levels on Intraocular Pressure and Systemic Health: Hormonal and Physiological Interactions in Female Dogs - Ozcan, Candemir; Safak, Tarik; Risvanli, Ali (Wiley, 2026)
Objective We hypothesized that variations in oestradiol and progesterone concentrations are significantly correlated with intraocular pressure (IOP) in female dogs and that this association is influenced by systemic physiological parameters such as age, body weight and blood pressure (BP). Animal studied This study was performed on 37 female dogs, aged between 1 and 7 years (median: 2.5 years, range: 1-7 years), with a mean weight of 23.15 +/- 9.72 kg. Procedures The relationships between right intraocular pressure (RIOP) and left (LIOP) with systolic and diastolic BP, serum oestradiol (E2) and progesterone (P4) levels were assessed. Additional factors, such as age, pulse and body temperature, were also analysed for their correlations with IOP and hormonal levels. Results Weak and insignificant positive correlations were noted between E2 and RIOP (r = 0.112, p = 0.255) and P4 and RIOP (r = 0.098, p = 0.283). No significant relationships were identified between E2, P4 and LIOP (E2: r = 0.242, p = 0.112; P4: r = 0.020, p = 0.460). A moderate positive association was identified between systolic BP and LIOP (r = 0.437, p = 0.003), whereas a slight positive correlation was noted between systolic BP and RIOP (r = 0.282, p = 0.045). Substantial negative associations were identified between P4 and systolic BP (r = -0.445, p = 0.010) as well as diastolic BP (r = -0.489, p = 0.005). A strong correlation was found between body weight and RIOP (r = 0.591, p < 0.001) as well as LIOP (r = 0.408, p = 0.006). Conclusion This preliminary study highlights that reproductive hormones like E2 and P4, along with factors such as age and body weight, significantly impact physiological parameters, including heart and ocular health in female dogs. Thus, variations in reproductive hormones and factors like age and body weight should be considered when evaluating ocular health in female dogs.
Keywords: dogs; hormonal influence; intraocular pressure; oestradiol; progesterone